The Rise of Human Rights Issue in the Post-Cold War World: The Vienna Conference (1993) - De Carvalho Hernandez, Matheus (The Age of Human Rights Journal, 2014)
This article aims to analyze the World Conference on Human Rights (Vienna, 1993) as a landmark in the human rights field. The goal is to discuss two hypotheses. First, that the Conference played an important role in the dissemination of human rights as an issue-area in international relations. Second, that the Conference contributed to the process of “relaxation of sovereignty”. The article is divided into three parts: the background to the Conference; the relationship between human rights and state sovereignty in the international system; the third section aims to connect the two hypotheses based on the debates of the Conference. The goal is not to analyze the Conference itself, but rather to demonstrate the trends that were empowered and unleashed by it in relation to the two hypotheses.